Pengaruh pemberian ekstrak daun kelor (Moringa oleifera Lam.) terhadap motilitas dan viabilitas spermatozoa tikus (Rattus norvegicus) dengan paparan panas - octavia, Arinda; Utomo, Budi; Madyawati, Sri Pantja; Suprayogi, Tri Wahyu; Sunarso, Agus; Hamid, Iwan Sahrial (Universitas Airlangga, 2021)
This study aimed to determine the effect of Moringa (Moringa oleifera Lam.) leaf extract on the viability and motility of spermatozoa of rats (Rattus norvegicus) exposed to heat (40 ºC). A total of 25 rats aged 2.5 months and weighed 200 grams were randomly divided into five groups. Rats in K (–) group were not exposed to heat and without Moringa leaf extract administration. Rats in K (+) group were exposed to heat (40 ºC) for 1 hour daily without Moringa leaf extract administration. Meanwhile, rats in P1, P2, and P3 groups were administrated with Moringa leaf extract 100, 200, and 400 mg/kg BW/day, then exposed to 40 ºC 1 hour daily for 14 days. The results showed that exposure to 40 °C one hour per day for 14 days in K (+) group caused a decrease (p <0.05) on viability and motility of rat spermatozoa compared to those of the K (–) group. The administration of Moringa leaf extract (P1, P2, and P3 groups) was followed by an increase (p <0.05) in viability and motility of rat spermatozoa compared to the K (+) group. Viability and motility of rat spermatozoa in the P3 group (given Moringa leaf extract 400 mg/kg BW/day and exposed to 40 ºC 1 hour daily for 14 days) were not significantly different (p >0.05) compared to the viability and motility of rat spermatozoa in K (–) group. It could be concluded that administration of Moringa leaf extract 400 mg/kg BW/day can maintain the viability and motility of spermatozoa in white rats exposed to heat.